Experimental Investigations of Injection and Combustion Parameters of a Homogeneous Charge Compression Ignition (HCCI) Engine with a Multi-Injection Common Rail System - Waleed Niklawy; Moatasem Shahin; Mohamed I. Amin; Ali Elmaihy (Communications - Scientific letters of the University of Zilina, 2022)
This work experimentally investigates the most imperative parameters that control the injection and combustion processes in a multi-injection HCCI Diesel engine namely; fuel-line pressure, timing of multi-injection events and the resulting in-cylinder pressure. These parameters in addition to the heat release rates are evaluated at different engine loads and speeds over up to 42 successive cycles. The main inter-relations of these parameters are also discussed. Results revealed that the maximum cylinder pressure and temperature in the HCCI engines are lower by 7% compared to similar conventional ones, which could lead to lower NOx emission. In addition, the fuel line pressure exhibits nearly the same major frequency of the waves, 850 to 950 Hz. Those results could be very useful for engine assessment, modeling, control, NOx reduction and power saving.